Habitus as foregrounded history: theorising affect in the social formation of embodied practice. Issue 2 (17th February 2019) - Leaney, Sarah
Abstract: This article builds upon a tradition of feminist critical engagements with Bourdieu, developing the concept of 'foregrounded history' as a way to conceptualise the temporal and affective in processes of habitus formation. Through analysis of affects 'produced through the social encounter' within everyday childhoods on a British council estate, the article explores habitus as histories both embodied and felt in the present. Drawing upon ethnographic research conducted within the interrelated fields of the Primary School and the Community Centre, this article considers processes of distinction, disagreement and resistance in the formation of classed positionings on The Estate.